Does anyone ever expect to die? - Anstey, Matthew; Watts, N.; Orford, N.; Seppelt, I.; Mitchell, I. (Australian Society of Anaesthetists, 2017)
Patients who come to the intensive care unit are amongst the sickest patients in our hospitals. Patients can be admitted to the intensive care unit unexpectedly (following accidents or sudden onset of illness) or as unplanned but not necessarily truly 'unexpected' admissions. These patients often have significant underlying chronic health issues, including metastatic cancer, advanced cardiac, respiratory, renal, or hepatic failure, or frailty, with a high likelihood of death in the ensuing months. Using the Australian and New Zealand Intensive Care Society Clinical Trials Group Point Prevalence Program, a prospective single-day observational study across 46 Australian hospitals in 2014 and 2015, we found that less than 9% of intensive care unit patients (51/577) had an advance directive available. From these results, we provide two suggestions to increase intensive care's understanding of patients' end-of-life wishes. First, systematically target 'high risk of dying' patient groups for goals of care conversations in the outpatient setting. Such groups include those where one would not be 'surprised' if they died within a year. Second, as a society, more conversations about end-of-life wishes are needed.